Food systems in depressed and contested agro-territories: Participatory Rural Appraisal in Odemira, Portugal - Horstink, Lanka; Schwemmlein, Kaya; Encarnação, Miguel F. (Frontiers in Sustainable Food Systems, 2023)
Farming regions in Europe, particularly in the South, are increasingly feeling the effects of climate change, e.g., drought, extreme weather events, and desertification, with severe consequences for food security and food sovereignty. Additionally, decades of rural mismanagement have left countless of these farming territories severely depressed. Finally, in the last decade, these agro-territories, already in a situation of social, economic, and ecological vulnerability, have found themselves amid competition for their natural resources between the model of traditional smallholder farming and that of large-scale intensive agriculture. This paper presents and discusses the results of a Participatory Rural Appraisal conducted in the region of Odemira, Southwest Portugal. Within the framework of an agroecological transition, the set of methodologies offered by the Participatory Rural Appraisal aims to support people in depressed and contested agro-territories to diagnose the state of their food systems and agroecosystems from a democratic and ecological point of view and engage those local actors in imagining fairer and healthier food futures for their regions. The mixed action research methodology selected for this study allowed, on the one hand, to identify the main challenges afflicting the region’s agriculture and food system while, on the other hand, bringing to light perceived tensions and convergences between different production models competing for resources. As the results of the present work show, these local tensions need to be addressed to jointly realise food democracy and food system sustainability.